Grain legumes increase yield stability in maize based cropping systems - Chimonyo, Vimbayi Grace Petrova; Snapp, Sieglinde S.; Chikowo, Regis (Wiley, 2019)
Functional crop diversity enhances crop productivity, stability, and food security through efficient nutrient cycling and water utilization; however, performance is variable under marginal environments. We applied stability analysis to assess impacts of grain legume integration on maize (Zea mays L.) grain yield, yield stability, N use efficiency (NUE), and ability to meet household protein requirements. Six field trials were conducted across three agroecological zones over five cropping seasons. We used additive main effect and multiplicative interaction to assess grain yield stability of maize in unfertilized maize, maize fertilized with 69 kg N ha−1 (Mz69), maize–pigeonpea [Cajanus cajan (L.) Millsp.] intercrop (MzPp), and maize in rotation with soybean [Glycine max (L.) Merr.] (SbRot), peanut (Arachis hypogaea L., PnRot), and peanut–pigeonpea intercrop (PnDLR). Maize in rotation or intercrop received 10.5 kg P2O5 and 35 kg N ha−1, whereas the Mz69 treatment received 21 kg P2O5 and 69 kg N ha−1. Maize grain yield in rotation with legumes was not significantly different from yield for Mz69. In wetter environments, MzPp intercrops had low maize grain yield (−35%) relative to Mz69, whereas in drier environments, maize had higher grain yield (14%) relative to rotated maize. Rotating maize with legumes increased NUE (56%) and protein contributions (65%) relative to Mz69. Grain yield of maize in SbRot consistently had the highest yield and was the most stable technology. Simple statistical models can be used to test multicrop stability. Integrating maize with legumes as intercrops or rotation can allow farmers to achieve high and stable yield under varying rainfall, with modest fertilizer investments.